Exploring the Influence of Employee Brain Predominance on the Perception of Leadership and Managerial Skills in the Mexican Labor Context - Leija González, Gerardo (Revista Internacional de Salarios Dignos, 2024)
This study examines how employees' brain dominance influences their perception of their superiors' leadership and their evaluation of managerial skills. We also analyze the implications of employees' perceptions and evaluations of managers in the Mexican labor market. A structural equation model was used with a representative sample of employees from different companies. The results show significant correlations between brain dominance, managerial skills and virtuous leadership of managers. In the same vein, specific connections between brain quadrants and leadership virtues were identified. These findings offer valuable theoretical and practical insights to better understand how cognitive preferences influence the perception of leadership and managerial skills. Acknowledging this cognitive diversity can help promote more inclusive, ethical and productive work environments in Mexico, thereby contributing to a more equitable, competitive and dynamic labor market.